Neuropathological protocol for the study of unexplained stillbirth - Roncati, Luca; Piscioli, Francesco; Pusiol, Teresa; Lavezzi, Anna M. (Folia Neuropathologica, 2017)
An updated neuropathological protocol for the examination of the nervous system in case of unexplained stillbirth has been elaborated and presented in this review. It is focused on the examination of the nervous centers located in the brainstem, which are involved in monitoring the vital functions. Only through a deep analysis of the brainstem it is possible to highlight developmental alterations of these essential centers, and then provide a plausible explanation of the pathogenetic mechanism behind the death. The guidelines, drawn up on the basis of numerous researches performed by the authors, include a histopathological protocol, with an indication of standardized samples, and an immunohistochemical protocol for the study of biological markers, frequently involved in these deaths. The main risk factors that can be related to the neuronal alterations are also reported, together with the indications for the toxicological examination, which should be possibly applied. The authors hope that this protocol will be soon adopted in all the institutions where a fetal death, after a routine autopsy procedure, is diagnosed as “unexplained”, in order to make standardized investigations on stillbirth. Nowadays, preventive strategies to decrease the incidence of these very distressing events for both parents and clinicians are necessary.